Remittances, Financial Development, and Growth - Ruiz-Arranz, Marta (IMF Working Papers; Working Paper, 2005)
There has been little systematic empirical study on the relationship between remittances and growth. This paper attempts to examine this relationship. Using a newly constructed crosscountry of data series for remittances covering a large sample of developing countries, we relate the interaction between remittances and financial development and its impact on growth. We analyze how a country's capacity to use remittances and its effectiveness in doing so might be influenced by local financial sector conditions. Given the difficulty of borrowing in developing countries, we explore the hypothesis that remittances can substitute for a lack of financial development and hence promote growth. The empirical analysis shows that remittances can promote growth in less financially developed countries. This relationship controls for the endogeneity of remittances and financial development using a Generalized Method of Moments (GMM) approach, does not depend on the particular measure of financial sector development used, and is robust to a number of sensitivity tests.